Study on effect of low calcium fly ash on geopolymer cement for oil well cementing - Sugumaran, M. (Society of Petroleum Engineers, 2015)
With the increasing awareness of global warming, geopolymer cement has been identified as one of the methods in reducing the emission of CO2 during oil well cementing operation. However, it is important that geopolymer cement can meet the specific requirement of oil well condition in order to be substitute of current conventional cement system. The use of fly ash in geopolymer based cement can affect the performance of the cement slurry by its properties which yet needs proper study to yield better advantages of it. In this research, the main objective is to study the effect of fly ash in geopolymer cement, by varying the properties which are thickening time, fluid loss and compressive strength. It is identified that the current conventional cement slurry is not environmentally-friendly, and is energy intensive. It is also identified that fly ash produced cannot be recycled and mostly being dumped. Thus, this study can provide the solutions to the problems identified. It involves extensive laboratory work in order to identify the properties of the cement. This project focused on the designation of fly ash based geopolymer cement compositions, the testing of the prepared fly ash based geopolymer with different compositions and different acid concentrations. This report comprises the literature review on the properties of geopolymers, the experimental works and their results, as well as the discussion and recommendations of the project. The tested parameters are water ratio, type and molarity of alkaline activator and alkaline activator ratio. The water ratio is 0.4 with the use of 12M of Sodium Hydroxide and the alkaline activator ratio is 0.4. Sodium silicate and silica fume was added to optimize the compressive strength which proved to have 31 increase of strength. Under low concentration acid, the cement is able to withstand the reaction but failed with higher concentration. The performance of the new blend will be analyzed. Copyright 2015, Society of Petroleum Engineers.